(untitled) (Jóvenes en la Ciencia, 2024)
The purpose of the article is to explore the possibilities of using artificial intelligence for the layout of book publications. The materials of the article focus on methods of automating the work of a specialist in the field of printing production during work on the layout of a book publication. In the course of the study, modern available technologies for working on textual and visual information were considered, ways of their use were given on the example of the stages of book layout. The article also raises questions of the ethics of using neural networks for full content generation and the problem of the lack of a mechanism for assigning copyright to created images and text. In addition, the prospects for the further use of artificial intelligence in the printing business as a whole and how it can affect the production process were considered. The article contains examples of already existing technologies and patents, which confirm the possibility of their implementation in the printing process.